The Childfree Phenomenon from the Perspective of Hadith in Islamic Family Law - Purwaningsih, Titin; Gusti, Hyang Kinasih (Program Studi Hukum Keluarga Islam Universitas Islam Negeri Raden Intan Lampung, 2025)
The childfree phenomenon has increasingly become a subject of debate among young Muslims in Indonesia and raises normative questions within Islamic family law. This study aims to analyze the childfree phenomenon from the perspective of Hadith-based Islamic family law through both normative and empirical approaches. The research employs a qualitative field study design conducted in Baradatu District, Way Kanan Regency, in 2026. Data were collected through in-depth interviews with Generation Z participants and analyzed using thematic analysis. Normative analysis was conducted through hadith takhrij, sanad and matn examination, and the framework of maqāṣid al-sharī‘ah. The findings reveal that Generation Z’s perceptions of childfree fall into three main orientations: rational-economic considerations, reproductive autonomy, and normative-religious perspectives. Normatively, the hadith encouraging marriage to fertile women reflects a procreative orientation as an ideal value rather than a binding obligation. Meanwhile, the hadith concerning the practice of coitus interruptus (‘azl) indicates flexibility in birth regulation as long as it does not intend permanent termination of lineage. Within the maqāṣid al-sharī‘ah framework, the protection of lineage (ḥifẓ al-nasl) encompasses not only quantitative continuity but also qualitative sustainability. Therefore, the childfree phenomenon cannot be judged in a binary legal framework; instead, it requires a proportional analytical approach that balances normative texts and social realities to preserve the authority of hadith while maintaining its relevance in contemporary Muslim family life.